EFFECT OF DIFFERENT SPACING AND FOLIAR SPRAY OF NUTRIENTS ON FLOWERING AND YIELD IN CASHEW UNDER ULTRA HIGH DENSITY PLANTING SYSTEM - M.S. ANEESA RANI,; N. KUMAR,; K. MURALI, (The Bioscan, 2021)
An experiment was conducted during 2013-2014 at Regional Research Station, TNAU, Vriddhachalam. The experiment was laid out in split plot design with main plot consisted of spraying of nutrients (M 1 ) and without spraying (M 2 ).The sub plot consisted of three different spacing 3 x 2 m (1666 plants ha -1 ), 4 x 2 m(1250 plants ha -1 ) and 5 x 4 m (500 plants ha -1 ). The results also revealed that the treatment (M 1 S 2 ) consisting of foliar spray of nutrients along with spacing (4 x 2 m) was found to be the best in increasing number of current season’s shoot (11.4 and 8.73 Numbers), number of panicles (35.5 and 118.5 numbers per m 2 ) and nuts yield (1.10 and 5.15 kg per tree) in cashew grown under ultra high density planting system.